The incorporation of objective criteria in compensation for medical negligence - Vargas Olivera, Elizabeth (2016)
The compensatory amounts set by the judges at the time of passing a judgment for cases of medical malpractice, despite constituting compensation to the victim for the damage this person has suffered, does not leave the result of what the law operator who considered convenient to establish as a prudent reason due to the absence of a reference parameter which delimits the compensatory damages in relation to the injury suffered, as it happens for example in the Compulsory Traffic Accident Insurance. Hence, it is necessary that the legislative level accepts a tabular system for cases of medical civil responsibility also to guide judges at the time of setting the compensatory damages, it allows a margin of equity to adapt it to each individual case in particular.